Hunger crisis and malnutrition in Pakistan: A word of caution - Mohamed Imthiyas, Umaira; Rizvie, Abdul Raheem; Mohamed Imtiyas, Muhammed Ifham (Journal of the Pakistan Medical Association, 2024)
Madam, Estimates from the 2022 Global Hunger Index (GHI) divulge a ‘moderate’ global hunger crisis level, although combat against hunger has reached an impasse, particularly in Pakistan, GHI is at a score of 26.1, under the serious category and extends beyond immediate food scarcity.1 It negatively impacts human health, as insufficient availability to sustenance induces malnutrition, depriving the body of necessary nutrients for proper functioning. Especially vulnerable to the ramifications are children. According to the GHI report, 29% of Pakistani children under the age of 5 are underweight and virtually 40% suffer from malnutrition.2 A key driver behind rise in childhood malnutrition is the surge in food prices. As demonstrated by the Sensitive Price Indicator (SPI) released by the Pakistan Bureau of Statistics for July, an increase of 29.83% in the year-on-year trend is seen, rendering in unaffordability of sustenance and essential nutrients for the general populace.3 Moreover, a survey of Sindh province in early 2020 shows that insufficient breastfeeding is a major amplifier of nutritional deficiency among children. The percentage of continuously breastfed infants under six months was 48% and just 58% of them up to two years. The percentage of continuously breastfed infants under six months was 48%, and just 58% were up to two years old.4 Inadequate breastfeeding can result in nutritional deficiency diseases like kwashiorkor, marasmus and various vitamin deficiencies. Another contributor, as observed by a study, concluded that one out of every ten children were unvaccinated due to maternal negligence to the purpose of vaccines or fear of the side effects that could present. This, coupled with poor food intake, can render immune-compromised children increasingly susceptible to pneumonia, diarrhoea and other ailments.5 As a significant portion of the problems stem from an absence in understanding, it is highly encouraged that parents obtain comprehensive guidance on the various facets of infant nutrition. This includes raising awareness about balanced diets, proper food preparation, and education programs promoting the benefits of breastfeeding and the critical importance of vaccines. Non-breastfeeding mothers should follow proper guidelines for using breast milk substitutes, as failing to comply with package instructions can reduce their children's nutritional benefits. Governments can help in tackling the crisis by sponsoring cost-effective nutritional packs that contain essential micronutrient supplementation, namely vitamins and minerals needed for healthy growth and development. ---Continue